Differences in Short-term Memory Before and After Exposure to Dangdut Music and Classical Music - Angela, Patricia; Firdaus, Jauhar; Parti, Dita Diana (International Journal of Health and Information System, 2024)
The quality of education in Indonesia is still relatively low when compared with other countries. To improve student achievement, stimulation can be provided to improve learning abilities and memory abilities. The learning and memory process will be optimal if a person is in an alpha brain wave state (8 to 12 Hz). Music that has a tempo of around 60 beats per minute, such as classical music, has the ability to stimulate alpha brain waves. Dangdut music is more familiar to Indonesian people and there is dangdut music which can change alpha brain waves to be more dominant. This type of research is a pre-experimental design with a crossover design. This research aims to see the differences between dangdut and classical music in improving short-term memory. The sampling technique used was purposive sampling with a sample size of 30 people. Short-term memory measurements were carried out before and after receiving music exposure for 30 minutes. Measurements were carried out using the digit span test method. The result was that there was a significant increase in short-term memory after exposure to dangdut and classical music. The conclusion of this research is that dangdut music and classical music both have an impact on improving short-term memory abilities equally well.